1999
DOI: 10.1007/s001130050374
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of superficial pes anserinus and partial rupture of patellar ligament as rare concomitant lesions of complex knee joint injuries

Abstract: We present a rare case of combined knee joint lesions in a 25 year old patient. Besides the commonly reported injuries of the knee joint due to directly applied valgus force, forceful quadriceps muscle contraction, external rotation at flexed knee causing combined lesions such as rupture of the anterior cruciate ligament, rupture of the posterior cruciate ligament and rupture of the medial collateral ligament, a rare combination of the above mentioned lesions and a rupture of the lateral meniscus, an osteochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The presence of avulsion injuries of the patella tendon enhanced our conviction that these injuries are due to high‐energy trauma. Injuries of the extensor mechanism occur very rarely in multiple ligament knee injuries [32, 33] and range from 6 to 15% [15, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of avulsion injuries of the patella tendon enhanced our conviction that these injuries are due to high‐energy trauma. Injuries of the extensor mechanism occur very rarely in multiple ligament knee injuries [32, 33] and range from 6 to 15% [15, 34].…”
Section: Discussionmentioning
confidence: 99%
“…We found that there is only one published case of pes anserine bursal rupture reported by Yagi S. et al (2019). The claims that there are two other reports published by Bruns J et al (1986) and Pointinger H. et al (1999) are not correct; on closer inspection, the two publications reported pes anserine tendon rupture and not pes anserine bursal rupture [5][6][7].…”
Section: Discussionmentioning
confidence: 75%